Cross‐Cultural Measurement Invariance of Adolescent Self‐Report on the Pediatric Quality of Life Inventory™ 4.0. (4th August 2015) - Stevanovic, Dejan; Atilola, Olayinka; Vostanis, Panos; Pal Singh Balhara, Yatan; Avicenna, Mohamad; Kandemir, Hasan; Knez, Rajna; Franic, Tomislav; Petrov, Petar; Maroco, João; Terzic Supic, Zorica; Bagheri, Zahra
Abstract : This study evaluated the cross‐cultural measurement invariance of the Pediatric Quality of Life Inventory version 4.0 (PedsQL ™ ) among adolescents sampled from Bulgaria, Croatia, India, Indonesia, Nigeria, Serbia, and Turkey. The multiple‐indicator multiple‐cause (MIMIC) model was used, which allowed controlling of demographic variables (i.e., age, gender, and socioeconomic status). Significant effects of country on scores within the PedsQL ™ domains were observed, with up to 17 items showing differential item functioning (DIF) across the countries. We did not find support for cross‐cultural measurement invariance hypotheses for scores on the PedsQL ™ adolescent self‐report in this study. Researchers should use caution in making cross‐cultural quality of life comparisons while using the PedsQL.